Peptide Biomaterials for Tissue Regeneration - Ross, Alex; Sauce-Guevara, Mildred A.; Alarcon, Emilio I.; Mendez-Rojas, Miguel A. (Frontiers in Bioengineering and Biotechnology, 2022)
Expanding the toolbox of therapeutic materials for soft tissue and organ repair has become a critical component of tissue engineering. While animal- and plant-derived proteins are the foundation for developing biomimetic tissue constructs, using peptides as either constituents or frameworks for the materials has gained increasing momentum in recent years. This mini review discusses recent advances in peptide-based biomaterials’ design and application. We also discuss some of the future challenges posed and opportunities opened by peptide-based structures in the field of tissue engineering and regenerative medicine.